A first‐in‐human oral dose study of mesdopetam (IRL790) to assess its safety, tolerability, and pharmacokinetics in healthy male volunteers. Issue 3 (20th May 2021) - Sjöberg, Folke; Waters, Susanna; Löfberg, Boel; Sonesson, Clas; Waters, Nicholas; Tedroff, Joakim
Abstract: The management of Parkinson's disease (PD) is frequently compromised by complications induced by dopaminergic treatment such as involuntary movements (dyskinesias) and psychosis. Mesdopetam (IRL790) is a novel dopamine D3 receptor antagonist developed for the management of complications of therapy in PD. This study evaluated the safety, tolerability, and pharmacokinetics of escalating single and multiple doses of mesdopetam. We conducted a prospective, single‐center, randomized, double‐blind, placebo‐controlled phase I, and first‐in‐human (FIH) study with mesdopetam administered to healthy male subjects. Overall, mesdopetam was well‐tolerated up to a 120 mg single dose and up to 80 mg upon multiple dosing. Adverse events (AEs) were mainly related to the nervous system and were dose‐dependent. No serious adverse events occurred and no AEs led to withdrawal. The results of the single‐ascending‐dose and multiple‐ascending‐dose parts indicated dose‐ and time‐independent pharmacokinetics with rapid absorption and maximum plasma levels that were generally reached within 2 h after dosing. No accumulation was observed upon multiple dosing. It is concluded that mesdopetam was safe and well‐tolerated in healthy male volunteers. Pharmacokinetic analysis indicated rapid absorption and dose‐linear pharmacokinetics of mesdopetam, with a plasma half‐life of around 7 h, upon single and repeated dosing. The pharmacokinetics of mesdopetam supports twice‐daily use in patients. Abstract : A first‐in‐human oral dose of mesdopetam for the management of Parkinson's Disease.